A Systematic Review of Blended Learning Strategies and Outcomes in Music Education - Zhang, Yifang; Beh, Wen Fen; Zhang, Chao (Harmonia: Journal of Arts Research and Education, 2024)
Educational technology has altered conceptions of effective learning. The combination of virtual and physical instruction is constantly developing and growing, making blended learning a growing trend. While blended learning has been extensively reviewed in various fields, there is a lack of research on its application in music education. This study aims to understand the current development of blended learning in the field of music education; this paper will collect literature on blended learning from the past ten years. Following the PRISMA guidelines, we have systematically analysed the blended learning strategies and outcomes in music education. This study examined Web of Science, Scopus, and ERIC for pertinent strings. Thirteen publications passed the strict screening procedure and were included in the analysis of blended learning in music education. This study found that the flipped classroom blended learning model has emerged as the prevailing method in music education, enhancing learners’ musical perception, performance, and overall experience. The findings reveal a need for more research on blended learning in music education.